Getting Around in the Technological World: An Extensive Analysis of Innovation and Organisational Systems Integration - Parmar, Harshil (Journal of Advanced Research in Humanities and Social Sciences, 2023)
This comprehensive review article explores the intricate interplay between organizational and technological systems, offering an in-depth examination of contemporary trends, challenges, and transformative opportunities shaping the landscape of modern business environments. As organizations increasingly navigate the complexities of the digital era, this review investigates key areas, including digital transformation, artificial intelligence, cybersecurity, collaborative technologies, blockchain, ERP systems, cloud computing, data analytics, organizational resilience, and human-computer interaction. The introduction underscores the growing significance of technological integration within organizational frameworks, setting the stage for an exploration into how cutting-edge technologies redefine operational paradigms and strategic objectives. By delving into the realm of digital transformation strategies, the review unveils how organizations harness digital technologies to augment efficiency, elevate customer experiences, and fortify their competitive positioning. Real-world case studies and success stories illuminate the tangible impacts of digital evolution across diverse industries. A dedicated section on artificial intelligence probes the depths of its integration in organizational processes, decision-making frameworks, and customer interactions. Considerations of AI adoption challenges, ethical implications, and future trajectories underscore the multifaceted nature of this transformative technology. Subsequently, the review scrutinizes the critical imperative of cybersecurity measures in an era marked by evolving cyber threats, dissecting the measures organizations employ to safeguard their data, systems, and intellectual assets.